Legal Protection for Unauthorized Copying of Songs on Digital Platforms Through Audio Watermarking Method - Baisuni, Hasan; Djulaeka, Djulaeka; Mohammad Ali Sajjad (JUSTISI, 2024)
The objective of this research is to investigate the effectiveness of the Copyright Law in safeguarding digital songs with audio watermarking from illegal duplication, and to analyze the legal responsibilities of those who duplicate songs on digital platforms using such methods under the Copyright Law. The research methodology employed is normative juridical, focusing on the internal aspects of positive law and utilizing literature sources like journals, books, case law, and relevant legislative materials, particularly Law No. 28 of 2014 on Copyright. Legal materials are gathered through a literature review as a secondary data source, along with descriptive analysis to elucidate the legal implications concerning copyright protection in the digital age. The novelty of this research lies in the integration of advanced and effective audio watermarking technology in addressing the challenges of copyright protection in the digital era. The research results highlight the importance of copyright protection in the music industry in the digital era. Audio watermarking methods are used to insert data into digital content to protect content ownership and identify copyright holders. There are efforts to overcome the challenges in preventing illegal acquisition of copyrighted content by utilising watermarking technology. It can thus be concluded that despite efforts made to regulate the digital marketplace and improve legal standards, illegal distribution of material is still quite rampant. YouTube is cited as an effective platform in protecting intellectual property rights by successfully addressing the issue of copyright infringement by removing infringing content.